Is There an “Acquired Idiopathic Head-Shaking Nystagmus”?—A Discussion of Mechanisms and Clinical Implications Based on a Case Report - Filippopulos, Filipp M.; Zwergal, Andreas; Huppert, Doreen (Frontiers in Neurology, 2022)
Background: Head-shaking nystagmus (HSN) occurs in both peripheral and central vestibular disorders. In most cases, HSN can be attributed to an asymmetric peripheral vestibular input or a structural lesion mostly in the cerebellum affecting the central velocity storage mechanism. An isolated HSN is very rare. Case presentation: We report on a young female patient with the clinical picture of recurrent episodes of vertigo, which were induced by fast head movements and were accompanied by a severe right-beating HSN with a long time constant of 60 s. There was no other clinical and instrument-based evidence of peripheral vestibular dysfunction (including video head impulse test, caloric test, vestibular-evoked myogenic potentials) or indication of a structural lesion in the nodulus, uvula or pontomedullary brainstem on fine-slice magnetic resonance imaging. She had no previous history of migraine, hearing deficits, or other focal neurological symptoms. Diagnostic criteria for vestibular paroxysmia, vestibular migraine, benign peripheral paroxysmal vertigo, or any other known vestibular disorders were not fulfilled. Chart review in the database of the German Center for Vertigo and Balance Disorders indicated eight additional patients with a similar clinical phenotype between 2018 and 2022. Conclusion: We propose a clinical entity called acquired idiopathic head shaking nystagmus (aiHSN) as a rare cause of episodic vertigo induced by fast head movements. Nystagmus characteristics suggest a subtle functional pathology of the central velocity storage mechanism in the nodulus and uvula, which is exacerbated during symptomatic episodes.